An Immunohistochemical Expressions of BAD, MDM2, and P21 in Oral Squamous Cell Carcinoma - Khalil, Afrah A; Sarkis, Seta A (Journal of Baghdad College of Dentistry, 2016)
Background: Oral squamous cell carcinoma (OSCC) is a common malignancy characterized by poor prognosis and low survival rate. The purpose of this study was to evaluate the Immunohistochemical expressions of BAD, MDM2, and P21as apoptotic markers in oral squamous cell carcinoma. Materials and methods: This study was performed on forty formalin-fixed paraffin-embedded blocks which histopathologically diagnosed as Oral Squamous Cell Carcinoma. All cases were collected from the Histopathological Laboratory from patients treated surgically at Maxillofacial surgery Department at Ramadi Teaching Hospital, Iraq. Results: The immunohistochemical staining of BAD showed positive expression in 39 (97.5%), MDM2 showed positive expression in 39(97.5%) and P21showed positive expression in 34(85%) of the collective cases. Conclusion: A statistically significant correlation was found regarding MDM2 with the tumor site, P21 with tumor grade.